A Study of Written English in Nepal - Singh, Ram Ekwal (Tribhuvan University Journal, 2020)
People in Nepal speak different languages. English is taught as a compulsory subject up to bachelor level. Writing skill in compulsory English occupies 40% weight age in class XI syllabus. This research was conducted with the main purposes of analysing the writing tasks and writing serves various purposes in a person’s everyday life. Its role is vital for upgrading students and job placement. It has been prescribed in English textbooks for higher secondary level across four subject streams and finding out the English teaching learning processes in the development of writing skills. The study had been delimited to the Kathmandu Valley. The sample comprised Class XI students. Mixed methods were utilized for gathering data such as questionnaire for students, test, students’ interview, teachers’ opinionnaire, teachers’ interview and class observation. All the higher secondary schoolteachers of English of the sample schools and 25 students of four streams were the respondents. The data was analysed using the Statistical Package for the Social Sciences (SPSS) version 16 and the t-test. The nature of exercises related to writing in textbooks of Class XI is almost similar, sequential and aims at developing creative writing. Science students performed the best of all on the test followed by Management, Arts and Education students. Almost all the informants expressed that writing grammatically correct sentences is of top most importance. Most of the teachers used process methodology in teaching writing. All informants interviewed expressed writing as a vital skill but it lacks separate classes.